The conditions of critical knowledge on capitalism or : the conflict between the economy and philosophy - Losoncz, Alpár (Array, 2019)
Beginning with a presentation of the asymmetry between philosophical and economic reflection, the article assesses the possible effects of practical philosophy in relation to the critical analysis of the independent economic domain. The article emphasizes the importance of political genealogy of capitalism which explains conceptual mutations leading to a) autonomisation of economic reflection, b) self-hegemonic economic reflection, c) domination of “real abstraction” that reflects not mental operations but social practice in capitalism. It is necessary to conceive differences between economics, the economy and economic domain, as well as to establish mediation between these domains. It is important not to perceive theoretical production as passive reflection in relation to reality, but to consider the theory as a constitutive-practical factor, as the condensation of certain social relationships. For economics (“dismal science”), this means that it is co-constitutive in relation to “economic reality”. Practical philosophy can contribute to the self-awareness of economic reflection in three domains: a) the relevance of ideology in relation to the autonomy of the economic sphere, b) the importance of the measure for the economizing, c) the form–substance problem. Based on the effects in the mentioned domains, practical philosophy could evoke the fact that the core of the economy is something that transcends the phenomenon of economy. The foundation of the economy is based on non-economic categories.